Survey Of Physical Fitness Players of SSB Karlos Malang, Aged 15 Years - Nailahya Arriza Shofan (Journal of Strength and Conditioning, 2024)
The aim of the researcher is to assess the level of physical fitness of the 15-year-old SSB Karlos Malang soccer school players with the TKJI test instrument for the 13-15 year age category. The researcher uses this type of quantitative descriptive research using survey techniques. The results of the TKJI test conducted on 15 subjects showed that there were 0 (0%) subjects who were in the "Less" category, 10 (67%) players were in the "Less" category, 5 (53%) players were in the "less" category Medium”, 0 (0%) players fall into the “Good” category, 0 (0%) players fall into the “Excellent” category. The researcher concluded that the physical fitness level of the 15-year-old SSB Karlos players was in the "Less" category and had an average score of 13.7